Caravanserais and their Role in Economic Interrelations of Central Asian Khanates (The 16th Century – the 1st Half of the 19th Century) - Gulchehra Azizovna Agzamova (International Journal on Integrated Education, 2022)
The article enlightens the role of caravanserais in Central Asian khanates, their types and specialization in the storage of certain products. It also focuses on the role of caravanserais as an in infrastructure in foreign relations, and emphasizes their influence on the social and economic development of khanates of Bukhara, Khiva and Kokand.